Surveillance of antibiotic resistance in Neisseria gonorrhoeae in the WHO Western Pacific Region, 2004 - WHO Western Pacific Gonococcal AMR Surveillance Programme; Tapsall, John (Communicable Diseases Intelligence, 2006)
The World Health Organization Western Pacific Region Gonococcal Antimicrobial Surveillance Programme (WHO WPR GASP) examined approximately 10,000 isolates of Neisseria gonorrhoeae from 15 countries for resistance to antibiotics in 2004. Treatment options for gonorrhoea in the Region are limited by persisting high rates of resistance to penicillins and quinolones. There were infrequent instances of spectinomycin resistance and the presence of gonococci with decreased susceptibility to third generation cephalosporins was again noted in several centres. Commun Dis Intell 2006;30:129–132.